2022
DOI: 10.2147/prbm.s359360
|View full text |Cite
|
Sign up to set email alerts
|

How Peer Abusive Supervision Affects Sales Employees’ Customer Knowledge Hiding: The Roles of Rivalry and Schadenfreude

Abstract: This study aims to examine the impacts of peer abusive supervision, perceived rivalry and schadenfreude over the abused peers on sales employees' customer knowledge hiding. Methods: We conducted multiple regression analyses of 283 sales employees' responses from two Chinese and two South Korean electronic device companies to test the hypotheses, which constitute a theoretical framework. Results: Our empirical results confirmed the positive impact of peer abusive supervision on sales employees' customer knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…In organizational contexts, the perceptions of injustice are very much visible and possess many detrimental outcomes. Recent studies determined certain elements that evoke employees’ KH behaviors when they perceive some sort of injustice such as role conflict, 5 workplace bullying, 122 and abusive supervision 40 . Secondly, this study fairly revealed the mediating role of employees’ SSB in the PIJ-KH relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In organizational contexts, the perceptions of injustice are very much visible and possess many detrimental outcomes. Recent studies determined certain elements that evoke employees’ KH behaviors when they perceive some sort of injustice such as role conflict, 5 workplace bullying, 122 and abusive supervision 40 . Secondly, this study fairly revealed the mediating role of employees’ SSB in the PIJ-KH relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies proposed that both personal and situational factors are important 40 and should be given due attention as it determines employees’ behaviors about unfair treatment, 41 injustice 42 and KH. 43 Thus, responding to such needs and recent calls in the literature, we contend that PIJ may have a potential in affecting individuals’ intentions to hide knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, organizations are dependent on the intellectual assets of its employees ( Kelloway and Barling, 2000 ), and several employees prefer not to share knowledge with others. Though employees have certain reasons of hiding knowledge at the workplace for example, workplace incivility and cynicism ( Anand et al, 2022 ), interpersonal injustice ( Cao, 2022 ), workplace bullying ( Islam and Chaudhary, 2022 ), and peer abusive supervision ( Ma et al, 2022 ) but KH also has some devastating consequences on both individuals and organizations ( Serenko and Bontis, 2016 ; Ellmer and Reichel, 2021 ; Nguyen et al, 2022 ). For instance, KH decreases creativity ( Černe et al, 2014 ; Bari et al, 2019 ), kills innovative work behavior ( Černe et al, 2017 ; Mubarak et al, 2022 ), and reduces employee performance ( Anand and Hassan, 2019 ).…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%